The Degree of Application of Meditative Thinking Skills Among Fifth Grade Learners in Social Studies "A Field Study in the Lattakia City " - أحمد, رفيف; ميساء حمدان (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of this research is to know the degree of application of meditative thinking skills among fifth grade learners in Social Studies in Lattakia city, to verify the objectives of the research, the descriptive approach was used and a test of meditative thinking skills was prepared, the research sample consisted of (268) male and female learners for the academic year 2022- 2023. The researcher reached several results, the most notable of which are: The fifth grade learners in the Lattakia City application of meditative thinking skills in Social Studies reached an average. The grades for fifth grade learners application of meditative thinking skills were average for the skills of (contemplation and observation, skill of detecting fallacies, arriving at conclusions, giving convincing explanation), and the skill of the skill of developing proposed solutions ranked fifth, with a low, there is a statistically significant difference regarding the application of meditative thinking skills among fifth grade learners as a whole each skill is studied separately in social studies according to the gender variable, in favor of females. The researcher presented several recommendations, the most important of which are: training basic education teachers to use meditative thinking skills in the educational process, especially social studies. The study plans include one or more subjects in teaching thinking in general and meditative thinking in particular.